A device for the on-line measurement of instantaneous swimming velocity - Kent, M. R.; Atha, J. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
In the study of the biomechanical characteristics of swimmers the measurement of intracyclic velocity fluctuations is of vital importance. To achieve full value, these measurements must meet certain requirements which may be summarized as follows: a) they should provide an accurate and continuous record of swimming velocity, b) the procedures involved should not impede the swimmer, and c) all records obtained should be synchronized to permit sensible interpretation. Over the past half-century only a limited number of procedures have been reported for measuring swimming velocity. They have involved both mechanical and optical methods of transduction and a variety of methods of recording.